2021
DOI: 10.14341/dm12484
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional indicators of the heart of patients with ischemic heart disease and type 2 diabetes mellitus. Rhythmoinotropic response isolated myocardium at different levels of glycated hemoglobin

Abstract: BACKGROUND: Adequate glycemic control can significantly reduce the risk of developing cardiovascular events. However, until now, glycaemic targets in aged patients remain a subject of discussion, especially in the conditions of the combined development of Type 2 Diabetes Mellitus (T2DM) and ischemic heart disease (IHD).AIMS: To examine the structural and functional heart parameters in patients with IHD associated with T2DM and the rhythmoinotropic responses of their isolated myocardium depending on glycated he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, the number of patients suffering from T2DM globally increases and this pathology more and more often is associated with other chronic diseases, in particular with coronary heart disease (CHD) [3,6,7]. The cohort study VALIANT has showed that T2DM is an independent predictor of unfavorable coronary events during the first year after myocardial infarction or patient death [4]. Our previous studies showed that CHD and T2DM comorbidity significantly affects cardiac remodeling at the cellular and molecular levels [1,2,5].…”
mentioning
confidence: 99%
“…Nowadays, the number of patients suffering from T2DM globally increases and this pathology more and more often is associated with other chronic diseases, in particular with coronary heart disease (CHD) [3,6,7]. The cohort study VALIANT has showed that T2DM is an independent predictor of unfavorable coronary events during the first year after myocardial infarction or patient death [4]. Our previous studies showed that CHD and T2DM comorbidity significantly affects cardiac remodeling at the cellular and molecular levels [1,2,5].…”
mentioning
confidence: 99%